The Effective Dose Analysis of Head CT-Scan on Adult Patients - Rahmadani, Febriana Dwi; Wibowo, R Arif; Ain, Khusnul (Universitas Airlangga, 2021)
This study was aimed to determine the difference of the effective dose from the clinical and theoretical on the head CT-Scan examination of adult patients and compare the data with the permitted dose limit from BAPETEN. The data collected at Haji Hospital Surabaya using MSCT Siemens Somatom Definition AS 64 Slice on five adult patients, aged between 28-67 years old. The step before the scanning process were adjusting the voltage (kV) and current values (mA) on the CT-Scan. The scanning duration for each patient was 4s and resulted in head images with CTDIvol and DLP values displayed on the monitor screen. The effective dose limit value for the head CT scan was 2.8 mSv, according to BAPETEN. The study results showed that the effective dose on head CT Scan examination was below the safe dose limit value, while the different fractions between the clinical and theoretical of Patient A, B, C, D, and E was 4.11%; 5.46%; 6.19%; 6.52%; and 5.42%, respectively.